Rare double-hit with two translocations involving IGH both, with BCL2 and BCL3, in a monoclonal B-cell lymphoma/leukemia. Issue 1 (December 2015) - Alpatov, Roman; Carstens, Billie; Harding, Kimberly; Jarrett, Carolyn; Balakhani, Sudabeh; Lincoln, Jessica; Brzeskiewicz, Peter; Guo, Yu; Ohene-Mobley, Alex; LeRoux, Jamie; McDaniel, Veronica; Meltesen, Lynne; et al.
Abstract Background Chronic Lymphocytic Leukemia (CLL) is a lymphoproliferative disease characterized by multiple recurring clonal cytogenetic anomalies and is the most common leukemia in adults. Chromosomal abnormalities associated with CLL include trisomy 12 andIGH;BCL3 rearrangement [t(14;19)(q32;q13)] that juxtaposes a proto-oncogenic geneBCL3 and an immunoglobulin heavy chain, a translocation that may be associated with shorter survival. In addition to theIGH;BCL3 rearrangement, other translocations involving 14q32 locus are involved in various lymphoproliferative pathologies pointing toward the significance ofIGH locus in oncogenic progression. Significantly, in the majority of B-cell neoplasms that carry anIGH;BCL3 rearrangement, it is a sole translocation involving anIGH locus. Case Presentation We report a patient who, in addition to trisomy 12, carried a rare double-hit translocation characterized by theIGH;BCL3 translocation and an additional clonalIGH;BCL2 translocation involvingIGH and another proto-oncogeneBCL2, t(14;18)(q32;q21), commonly found in follicular lymphoma. Further single nucleotide polymorphism (SNP) array-based analysis detected a duplication of the 58.8 kb region at 19q13.32 adjacent to theBCL3 translocation junction on chromosome 19q13. Interestingly, the duplicated region containedERCC2 gene, which encodes a DNA excision repair protein involved in the cancer-prone syndrome, xeroderma pigmentosum. Conclusions Taken together our findings indicate the existence of double-translocation driven oncogenic events involving bothIGH loci and proto-oncogenesBCL2 andBCL3 . Importantly, theIGH;BCL3 translocation was characterized by the duplication of the genomic region adjacent toBCL3, containing a major DNA repair factor, ERCC2 .